Therapeutic Efficacy and the Impact of the “Dose” Effect of Acupuncture to Treat Sciatica: A Randomized Controlled Pilot Study - Liu CH; Kung YY; Lin CL; Yang JL; Wu TP; Lin HC; Chang YK; Chang CM; Chen FP (Journal of Pain Research, 2019)
Ching-Hsiung Liu,1,2 Yen-Ying Kung,2–4 Chun-Liang Lin,1 Jen-Lin Yang,2–4 Ta-Peng Wu,3 Hong-Chun Lin,3 Yang-Kai Chang,3 Ching-Mao Chang,2–4 Fang-Pey Chen2,3 1Department of Neurology, Lotung Poh-Ai Hospital, Ilan, Taiwan, Republic of China; 2Institute of Traditional Medicine, School of Medicine, National Yang-Ming University, Taipei, Taiwan, Republic of China; 3Center for Traditional Medicine, Taipei Veterans General Hospital, Taipei, Taiwan, Republic of China; 4Faculty of Medicine, School of Medicine, National Yang-Ming University, Taipei, Taiwan, Republic of ChinaCorrespondence: Fang-Pey ChenInstitute of Traditional Medicine, School of Medicine, National Yang-Ming University, and Director, Center for Traditional Medicine, Taipei Veterans General Hospital, Number 155, Section 2, Linong Street, Taipei 112, Taiwan, Republic of ChinaTel +8862-2875-7454Fax +8862-2875-7452Email fpchen@vghtpe.gov.twPurpose: To investigate the required sample size for and feasibility of a full-scale randomized controlled trial examining the impact of the “dose” effect of acupuncture in treating sciatica.Patients and methods: Fifty-seven patients with sciatica, aged 35–70 years, were recruited and screened. Thirty-one participants were randomly assigned to receive “low-dose” manual acupuncture (MAL) (n= 15) or “high-dose” manual acupuncture (MAH) (n=16). The acupuncture treatment was administered twice weekly for 4 weeks. The primary outcome was the visual analog scale (VAS) score at baseline and after 4 weeks of acupuncture treatment. Secondary outcomes included the Roland Disability Questionnaire for Sciatica (RDQS), the Sciatica Bothersomeness Index (SBI), and the World Health Organization Quality of Life in the Brief Edition (WHOQOL-BREF) scores at baseline and after 4 weeks of acupuncture treatment.Results: Thirty patients completed the study. For all patients, acupuncture achieved significant improvement in the VAS (5.48±2.0, p<0.001), RDQS (3.18±2.83, p=0.004), and SBI (2.85±3.23, p=0.008) scores, but not in the WHOQOL-BREF scores. In the between-group analysis, the assessed scales showed no significant differences between the MAL and MAH groups. However, based on the level of chronicity, the MAH group demonstrated greater improvement in the outcomes and a significant benefit in the physical subscale of the WHOQOL-BREF (p<0.05).Conclusion: Results of this pilot study indicate that acupuncture is safe and may effectively relieve symptoms and disability in patients with non-acute sciatica. MAL was as effective as MAH in treating sciatica. A subsequent trial with a larger sample size (estimated at n=96) is required to confirm whether patients with a high level of chronicity would benefit from MAH treatment.Trial registration: NCT03489681.Keywords: acupoints, alternative medicine, chronic pain, low back pain, analgesia, noninvasive treatment